Three new species of the genus Brachinus Weber, 1801 from the Philippines, with a modified key to species (Coleoptera: Carabidae: Brachininae) - Tian, Mingyi; Deuve, Thierry (Zootaxa, 2013)
Three new Brachinus species namely B. grootaerti n. sp. (Palawan Island), B. palawanensis n. sp. (Palawan Island), B. mindanaoensis n. sp. (Mindanao Island) from Philippines were described. In addition, a modified key to the known Brachinus Philippine species is provided.